CFEL–ASG Software Suite (CASS): usage for free‐electron laser experiments with biological focus. Issue 4 (23rd June 2016) - Foucar, Lutz
Abstract : An overview of how the well established CFEL–ASG Software Suite ( CASS ) can be used for serial femtosecond crystallography data is given. Abstract : CASS [Foucar et al. (2012). Comput. Phys. Commun. 183, 2207–2213] is a well established software suite for experiments performed at any sort of light source. It is based on a modular design and can easily be adapted for use at free‐electron laser (FEL) experiments that have a biological focus. This article will list all the additional functionality and enhancements of CASS for use with FEL experiments that have been introduced since the first publication. The article will also highlight some advanced experiments with biological aspects that have been performed.